Fractional iron absorption from enteric-coated ferrous sulphate tablet - Thankachan, Prashanth (Indian J Med Res, 2020)
BACKGROUND & OBJECTIVES: Iron supplementation is widely used public health measure to manage iron deficiency anaemia. In India, enteric-coated iron tablets are administered to adolescent boys and girls to avoid adverse effects such as gastritis, which reduces compliance, but this may result in poor iron absorption. Data on the absorption of iron from enteric-coated ferrous sulphate tablets are lacking. The present study using stable isotopic approach was aimed to measure iron absorption in iron deficient women. METHODS: Iron absorption was measured from stable isotope-labelled enteric-coated ferrous sulphate ((57)Fe, ECFS) and uncoated ferrous sulphate ((58)Fe, UCFS) tablets in iron-deficient (n=9) women, aged 18-40 yr with no infection or inflammation. The two types of tablets (ECFS and UCFS) were administered on consecutive days, 60 min after breakfast, and the sequence being random. Blood samples were collected before dosing, and on day 15, to measure iron absorption from the shift in iron isotopic ratios in haemoglobin. RESULTS: Eight women completed the iron absorption study. Iron absorption was found to be significantly lower in ECFS compared to UCFS (3.5 vs. 12%, P<0.05) consumption. INTERPRETATION & CONCLUSIONS: Our study showed poor iron bioavailability from ECFS, and supplementation programmes may consider UCFS tablets for better haematological outcomes.